Impact of sedimentation to sponge on coral reef ecosystems in Hoga and Sampela Island, Wakatobi Archipelago - Sakaria, Fajria Sari; Haris, Abdul; Massinai, Arniati (Torani Journal of Fisheries and Marine Science, 2018)
Sponge is marine organism from porifera phylum which is a filter feeder (filtering food). Sponge can be degraded by high sediment suspended seawater, which causing a sponge body blockage, which will inhibit the growth of the sponge and even experienced death. This study aims to analyze the sponge coverage, sponge species identification and the relationship between sponge coverage and sedimentation rate. Underwater Photo Transect (UPT) was used in this study at three (3) depths i.e. 3 m, 6 m, and 10 m. The results showed that sponge coverage in high sedimentation rate is lower and there are 17 sponge species were found which were divided in to 14 family. In addition to sedimentation, water quality also greatly affects sponge coverage, such as currents, dissolved organic matter, salinity, and turbidity. One cause of sedimentation comes from the land, such as the transfer of land functions. Sponge's existence will continue to be threatened by physical and chemical pressure, and sedimentation if exploitation cannot be controlled.Keywords: sponge, sedimentation, water quality, land change